A study on the construction of identity of female cadets in the Philippine Military Academy - Antonio, Mark Erwin B.; Collado, Regienald L. (2009)
The study focused on Philippine Military Academy's female cadets' construction of identity through their communicative behaviors and self-presentation. It also intends to know whether they are cognitively complex individuals through Constructivism Theory. Via PMA Administration for Academic Affairs(PMAAA) recommendation, the academy provided fifteen (15) first class and twenty-two(22) second class female cadets as respondents. To generate information, the study utilized open-ended survey questionnaires, focused group discussion(FGD) and observation. Result show that the PMA culture influences female cadets' construction of their identity. In this way, respondents identity themselves with PMA's values, principles, norms and protocols reflecting on their cognitive complexity -- Author's abstract.